Zakat In Malaysian rural development: issues and potentials - Mahamod, Lukman Hakim; Jaafar, Samsuddin; A. Rahman, Muhammad Ali (Art University of Iran and International islamic University of malaysia, 2013)
The earning power for sustenance and non-sustenance of the rural poorest and poor has been ignored in existing programmes for alleviating rural poverty because the funding used is oriented to the capitalist ideology. Zakat is a different system based on existing funding to provide sustenance and non-sustenance to the poorest, who are eligible to receive zakat as long as they are classified as faqir or miskin. In Malaysia, the federal government has been unable to use zakat for poverty alleviation at the national level because the administration of this tax is the responsibility of individual states. Although efforts have been made to centralize the administration of zakat for the benefit of poor states, the idea has been rejected by most states. One of those most resistant to centralization has been Kedah. Kedah is one of the poor states in Malaysia, where the majority are Malays (Muslim) and whose occupations are mostly in poor sectors of the economy, particularly padi and rubber. The effectiveness of poverty alleviation also depends on a sufficient amount of zakat collected. The centralization of zakat collection to the Kedah Department of Zakat (KDoZ) headquarters, however, has been of benefit to the poor districts.